Mapping the interface of poverty, emerging markets and zoonoses - Grace, Delia (International Livestock Research Institute, 2012)
Mapping and measuring burden and risk of zoonotic diseases is important for effective targeting and resource allocation. A study commissioned by the Department for International Development, UK brought together veterinarians, medics, geographers and economists to map systems where investment in control of zoonotic diseases could bring greatest benefit to poor people. The study had several elements: we updated global maps of the number and density of poor livestock keepers; we used a macro-economic model (IMPACT) to predict and map the livestock systems undergoing most rapid change in response to market demand; we updated the map of emerging disease events by Jones et al. (2008); we conducted a literature review identifying over 1,000 studies to map the burden of endemic zoonoses; and, we extracted data on zoonotic disease from the World Health Organisation Global Burden of Disease. The resultant portfolio of maps and underlying data allowed us to map zoonoses at the interface of poverty and emerging markets. We identified 13 zoonoses responsible for most of the health and economic burden to poor people and also identified 22 countries, which bear most of the burden of zoonotic diseases. Finally, we identify regions and countries where investments in zoonoses control are most likely to pay off for the poor (South Asia followed by East-Central Africa followed by South East Asia in terms of regions.) This study demonstrates how trans-disciplinary teams can bring together knowledge from different disciplines to answer bigger questions of practical importance to decision-makers.